2021
DOI: 10.1186/s12935-021-02202-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and diabetes: the interlinking metabolic pathways and repurposing actions of antidiabetic drugs

Abstract: Cancers are regarded as one of the main causes of death and result in high health burden worldwide. The management of cancer include chemotherapy, surgery and radiotherapy. The chemotherapy, which involves the use of chemical agents with cytotoxic actions is utilised as a single treatment or combined treatment. However, these managements of cancer such as chemotherapy poses some setbacks such as cytotoxicity on normal cells and the problem of anticancer drug resistance. Therefore, the use of other therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 262 publications
0
16
0
2
Order By: Relevance
“…Moreover, hypoglycemia caused by impaired glucose uptake could be another trigger for induction of apoptosis. Hypoglycemia has been demonstrated to cause a decrease in ATP production associated with the induction of apoptosis ( 65 , 66 ). Our experimental findings do not indicate a direct implication of glutor in the modulation of mitochondrial functions such as mitochondrial membrane potential; however, our results suggest the role of glutor-modulated p53 expression in the implication of altered mitochondrial membrane polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypoglycemia caused by impaired glucose uptake could be another trigger for induction of apoptosis. Hypoglycemia has been demonstrated to cause a decrease in ATP production associated with the induction of apoptosis ( 65 , 66 ). Our experimental findings do not indicate a direct implication of glutor in the modulation of mitochondrial functions such as mitochondrial membrane potential; however, our results suggest the role of glutor-modulated p53 expression in the implication of altered mitochondrial membrane polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming is a hallmark of both diabetes and cancer, which is presented with similar abnormalities in glucose, fatty acid, and cholesterol metabolisms ( 46 ). DPP4 has been identified as a potential regulator that links enhanced cancer risk with metabolic diseases such as hyperglycemia and obesity ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…As insulin is a growth factor, the unabsorbed insulin poses health risks. It can promote tumor development in the colon through activating the RAS-MAPK and PI3K-AKT-mTOR signalling pathways which are associated with tumor proliferation, epithelial–mesenchymal transition and survival [105,106]. Epidemiological and preclinical studies have indicated that hyperinsulinemia plays a role in the development of cancer.…”
Section: Mucosa-penetrating Strategiesmentioning
confidence: 99%